Very Low Numbers of CD4(+)FoxP3(+) Tregs Expanded in Donors via TL1A-Ig and Low Dose IL-2 Exhibit a Distinct Activation / Functional Profile and Suppress GVHD in a Pre-clinical Model - Copsel, Sabrina (Biol Blood Marrow Transplant, 2018)
Regulatory T cells (Tregs) are essential for the maintenance of tolerance and immune homeostasis. In allogeneic hematopoietic stem cell transplantation (aHSCT), transfer of appropriate Treg numbers is a promising therapy for the prevention of graft-versus-host disease (GVHD). We have recently reported a novel approach which induces the marked expansion and selective activation of Tregs in vivo by targeting TNF receptor superfamily 25 (TNFRSF25) and CD25. A potential advance to promote clinical application of Treg cells to ameliorate GVHD and other disorders would be the generation of more potent Treg populations. Here we wanted to determine if very low doses of Tregs generated using the ‘two-pathway’ stimulation protocol via TL1A-Ig fusion protein and low dose IL-2 (targeting TNFRSF25 and CD25, respectively) could be used to regulate pre-clinical GVHD. Analysis of such ‘two-pathway’ expanded Tregs identified higher levels of activation / functional molecules (CD103, ICOS-1, Nrp-1, CD39, CD73, il-10, and tgfb1) vs. unexpanded Tregs. Additionally, in vitro assessment of ‘two-pathway’ stimulated Tregs indicated enhanced suppressor activity. Notably, transplant of extremely low numbers of these Tregs (1:6 expanded Tregs / Tconventional) suppressed GVHD following an MHC-mismatched aHSCT. Overall, these results demonstrate that ‘two-pathway’ stimulated CD4(+)FoxP3(+) Tregs were quantitatively and qualitatively more functionally effective than unexpanded Tregs. In total, the findings in this study support the notion that such ‘two-pathway’ stimulated Tregs may be useful for prevention of GVHD and ultimately promote more widespread application of aHSCT in the clinic.